Analisis Kinerja Keuangan Daerah Kabupaten Jayapura (Studi Kasus Komparasi Kinerja Bupati Kabupaten Jayapura Periode 2012 -2016 Dan 2017-2019) - Transna Putra Urip; Herlisya Fernilita Patty (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2022)
This research was compiled with the aim of knowing and analyzing the financial performance of the Regional Government of Jayapura Regency in 2012–2019 and knowing whether there is a difference between the performance of the Regional Head of Jayapura Regency in periods 1 (2012–2016) and 2 (2017–2019) held by Mr. Matthew Awoitauw, S.E., M.Sc. Data analysis used financial ratios, namely the ratio of regional financial independence, the ratio of regional financial dependence, the ratio of effectiveness of local original income, and the ratio of the degree of decentralization, in addition to using the average different test. The research results show that (1) the ratio of regional financial independence shows an average value of 7.38% (instructive relationship pattern), and (2) the results of the t-test show that there is no difference between the performance of periods 1 and 2. (2) The ratio of regional financial dependence shows an average value of 90.80% (a very high category), and the results of the t-test show that there is no difference between performance in periods 1 and 2. (3) The ratio of effectiveness of regional original income shows an average value of 95.15% (this category is quite effective), and the t-test shows that there is a difference in the performance of regional heads between periods 1 and 2. (4) The ratio of degrees of decentralization shows an average value of 6.70% (very poor category), and the t-test shows that there is no difference between the performance of regional heads in periods 1 and 2. Keywords: financial performance, financial ratios, period, differences